Analysis of RUNX1 binding site and RAPTOR polymorphisms in psoriasis: no evidence for association despite adequate power and evidence for linkage. Issue 1 (27th May 2005) - Stuart, P; Nair, R P; Abecasis, G R; Nistor, I; Hiremagalore, R; Chia, N V; Qin, Z S; Thompson, R A; Jenisch, S; Weichenthal, M; Janiga, J; Lim, H W; et al.
Abstract : Background: A previous study identified two peaks of allelic association between psoriasis and single nucleotide polymorphisms (SNPs) mapping to distal chromosome 17q, including a disease associated SNP that leads to loss of a RUNX1 transcription factor binding site, and additional SNPs in the third intron of the RAPTOR gene. Another study found an association with SNPs in the RAPTOR gene, but not with the RUNX1 binding site polymorphism. Methods: In an effort to confirm these observations, we genotyped 579 pedigrees containing 1285 affected individuals for three SNPs immediately flanking and including the RUNX1 binding site, and for three SNPs in the RAPTOR gene. Results: Here we report further evidence for linkage to distal chromosome 17q, with a linkage peak mapping 1.7 cM distal to the RUNX1 binding site (logarithm of the odds 2.26 to 2.73, depending upon statistic used). However, we found no evidence for association to individual SNPs or haplotypes in either of the previously identified peaks of association. Power analysis demonstrated 80% power to detect significant association at genotype relative risks of 1.2 (additive and multiplicative models) to 1.5 (dominant and recessive models) for the RUNX1 binding site, and 1.3 to 1.4 for the RAPTOR locus under all models except dominant. Conclusions: Our data provide no support for the previously identified RUNX1 binding site or for the RAPTOR locus as genetic determinants of psoriasis, despite evidence for linkage of psoriasis to distal chromosome 17q.